IDENTIFICATION CUSTOMS EXAMINATIONS IN THE LIGHT OF INNOVATIONS IN FIBRE TECHNOLOGY - SAPOZHNYK, Dmytro; PELYK, Lesya (Herald of Khmelnytskyi National University. Economic sciences, 2025)
Development of uniform approaches in all areas of interaction and activities of the structural units of the State Customs Service, in particular, with regard to the application of HS. The article presents the results of the study and analysis of problematic issues of customs identification examinations in the light of modern innovations in fibre materials technology. It is shown that goods of Sections VIII, X, XI, XI and XII of the HS are mainly made of fibrous materials - leather fibres, cellulose fibres, textile fibres - clothing, footwear, haberdashery, bags, accessories, etc. When conducting identification examinations of these particular goods, it is important to have a scientifically sound methodological basis and a uniform approach to conducting identification research. The absence of a unified methodological development to date often entails a certain risk during identification and the possibility of error, which, as you know, leads to negative court practice and a shortfall in customs payments. In the process of conducting customs examinations, customs experts face a number of problems of identification based on the organoleptic assessment of external inspection in accordance with the HS of goods made of natural and "composite leather", since sometimes "composite leather" has an external resemblance to natural leather, especially to a split of natural leather, and modern technologies make it possible to obtain new materials with improved mechanical properties and a "living" structure of the front surface from low-quality union. The article analyses the factors influencing the results of the identification examination of goods under HS (optimal number of identification features; sufficient number of research methods; consistency in the use of uniform terminology in the description of goods and identification features). The author concludes that there is a need to develop unified approaches to issues related to terminology concerning the characteristics of goods which ensure their safety and quality, and which are regulated by regulatory documents and make it impossible to make a mistake, i.e., incorrect classification and, accordingly, unlawful application of tariff regulation measures of foreign economic activity.